From Peers to Lay Bystanders: Findings from a Decade of Naloxone Distribution in Pittsburgh, PA. Issue 3 (27th May 2018) - Bennett, Alex S.; Bell, Alice; Doe-Simkins, Maya; Elliott, Luther; Pouget, Enrique; Davis, Corey
ABSTRACT: Distribution of the opioid overdose reversal drug naloxone has been central to efforts to combat the ongoing opioid epidemic in the United States. This report presents data from Prevention Point Pittsburgh (PPP), a public health advocacy and direct service organization that has operated an overdose prevention program (OPP) with naloxone distribution since 2005. The program initially provided naloxone training and distribution only to people who use opioids (PWUO). In 2015, a change to state law enabled PPP to provide naloxone to anyone in a position to respond to an opioid-related overdose. This report examines the characteristics and naloxone-related experiences of 1330 PWUO trained in overdose prevention and naloxone administration by PPP between January 1, 2006, and December 31, 2015, and compares rates of return for a naloxone refill by PWUO and the 619 non-users trained between January 1, 2015, and December 31, 2015. While larger numbers of individuals obtained naloxone after state law changed, PWUO—especially heroin users—were significantly more likely to reverse an overdose and return to PPP for a naloxone refill. Based on these findings, we recommend that resource-limited, community-based organizations prioritize the distribution of naloxone to PWUO.